Natural killer cell cytotoxicity is a predictor of outcome for patients with high risk myelodysplastic syndrome and oligoblastic acute myeloid leukemia treated with azacytidine. Issue 10 (24th August 2019) - Tsirogianni, Maria; Grigoriou, Eirini; Kapsimalli, Violetta; Dagla, Kleopatra; Stamouli, Maria; Gkirkas, Konstantinos; Konsta, Eve; Karagiannidou, Angeliki; Gkodopoulos, Konstantinos; Stavroulaki, Georgia; Pappa, Vassiliki; Angelopoulou, Maria; et al.
Abstract: The aim of the present study was to identify biomarkers predictive of the outcome of patients with high-risk myelodysplastic syndrome and oligoblastic acute myeloid leukemia (AML) treated with 5-azacytidine (AZA). We prospectively examined the association between NK-cytotoxic activity, myeloid-derived suppressor cells (MDSCs), and T-regulatory cells (Tregs) on the overall survival (OS) of patients. Patients with NK-cytotoxicity above a critical threshold had a longer duration of response and survived longer than patients with severe impairment of NK-cytotoxicity. The numbers of MDSCs, and Tregs in the PB of patients after a short exposure to AZA were not different from normal donors. In conclusion, the results of our study suggest that the therapeutic activity of AZA is at least partly mediated by an immunomodulatory effect. To our knowledge, this is the first study reported so far, that shows a positive correlation between NK cytotoxicity and OS of AZA-treated patients.